(untitled) (Bangladesh Journal of Animal Science, 2012)
The chemical and bacteriological qualities of popular Dahi collected from six areas of Bangladesh were evaluated. The areas were Dhaka (Savar), Rajshahi (Bogra), Khulna, Barishal (Gauronadi), Chittagong (Comilla) and Sylhet. Traditionally made 24 Dahi samples, 4 in each area, were collected and analyzed for chemical and bacteriological qualities. Acidity, pH, ash and protein content of Dahi were found insignificant difference among the samples of different areas. However, significance differences in chemical parameters (fat and sugar) were observed. The higher total viable bacteria and coliform count were found in Bogra region. An overall analysis of the results of this study revealed that the Dahi collected from selected areas were of acceptable quality. However, their sugar and ash content were very high. http://dx.doi.org/10.3329/bjas.v41i1.11977